Antioxidant and Antimicrobial Potential of Sappan Wood Extract against Porphyromonas gingivalis - Sugiaman, Vinna Kurniawati; Jeffrey, Jeffrey; Widowati, Wahyu; Ferdiansyah, Rival; Novianto, Agung (Faculty of Medicine, Universitas Padjadjaran, 2024)
Gingivitis inflammation triggered by microbial biofilms is one of the detrimental causes of periodontal diseases. When a periodontal disease occurs, tooth decay becomes inevitable, and can pose a serious threat to oral health, requiring appropriate treatment. Inflammation in periodontitis is mainly caused by oxidative stress; hence, antimicrobial and antioxidant-based therapies are suggested for periodontitis. Sappan wood is well-known for its brazilin compounds, which have the potential as herbal medicines and antibacterial agents to fight oral pathogens with minimal side effects. This study aimed to examine the antimicrobial and antioxidant activities of sappan wood extract (SE) as a candidate agent for preventing periodontal diseases. This study was conducted at Maranatha Christian University, Sekolah Tinggi Farmasi Indonesia, and Aretha Medika Utama from January-April 2023. The sappan wood was extracted using ethanol 96% and the antimicrobial evaluation was done by calculating the total colony of P. gingivalis while the antioxidant activity was evaluated by ABTS, H2O2, and FRAP Assays. This study revealed that SE was significantly effective in reducing the total colony of P. gingivalis up to 0 CFU/mL. The highest antioxidant activity of SE was found in 100 µg/mL with IC50 19.06 µg/mL for ABTS, 90.99 µg/mL for H2O2, and 564 µM Fe (II) for FRAP. Thus, SE presents its strong antimicrobial and antioxidant activity potentials by in vitro evaluation that could be analyzed further for its utilization as a periodontal-preventing agent. This study also provides basic information for future implication of sappan wood extract as ingredients for dental care products.